2005
DOI: 10.1021/jp045551g
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Cell Potential Method To Predict Phase Equilibria of Multicomponent Gas Hydrate Systems

Abstract: We present the application of a mathematical method reported earlier 1 by which the van der Waals-Platteeuw statistical mechanical model with the Lennard-Jones and Devonshire approximation can be posed as an integral equation with the unknown function being the intermolecular potential between the guest molecules and the host molecules. This method allows us to solve for the potential directly for hydrates for which the Langmuir constants are computed, either from experimental data or from ab initio data. Give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 51 publications
4
67
0
Order By: Relevance
“…In the case of argon, methane, ethane, cyclo-propane, propane and iso-butane, the values of V min K;t calculated here are consistent with the well depth of the cell potentials used previously by Anderson et al [7,8], as shown in Table 5. However, it should be noted that the different potential energy surfaces show that, except for Ar, the five other molecules cannot freely rotate inside the clathrate cage.…”
Section: Calculation and Fit Of The Langmuir Constantssupporting
confidence: 90%
See 4 more Smart Citations
“…In the case of argon, methane, ethane, cyclo-propane, propane and iso-butane, the values of V min K;t calculated here are consistent with the well depth of the cell potentials used previously by Anderson et al [7,8], as shown in Table 5. However, it should be noted that the different potential energy surfaces show that, except for Ar, the five other molecules cannot freely rotate inside the clathrate cage.…”
Section: Calculation and Fit Of The Langmuir Constantssupporting
confidence: 90%
“…It is thus obvious from Eq. (7) that, in contrast to the simplified central-well potential approach [8], any analytical integration would be intractable here due to the asymmetries of the host lattice cages and of the guest molecule itself.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations